Pregnancy rates following three different timings of intrauterine insemination for women with unexplained infertility: A randomised controlled trial - Samah AboulGheit (Middle East Fertility Society Journal, 2010)
Objective: To compare pregnancy rates following three different timings of intrauterine insemination after human chorionic gonadotrophin administration at 24, 34 and 48h in women with unexplained infertility. Setting: Kasr El-Aini Hospital. Design: Randomized controlled trial. Participants and methods: Couples with unexplained infertility had 125 cycles of IUI divided in three groups: Group (1): 24h after hCG administration, Group (2): 34h after hCG administration and Group (3): 48h after hCG administration. Results: There was no significant difference in pregnancy rates between all groups, Group 1 vs. Group 2 OR=0.61, 95% [CI] 0.15–2.36, Group 1 vs. Group 3 OR=0.42, 95% CI 0.12–1.53 and Group 2 vs. Group 3 OR=0.729, CI 0.23–2.32. Conclusion: IUI can be done any time between 24 and 48h after hCG injection without significant differences in pregnancy rates.